Simultaneous metabolism of benzoate and photobiological hydrogen production by Lyngbya sp. (September 2016) - Shi, Xian-Yang; Yu, Han-Qing
Abstract: Cyanobacteria are an inexpensive and sustainable source of photobiological H2 production due to their simple nutritional conditions. Combination of toxic contaminant degradation with H2 production is a promising approach in wastewater treatment. This study demonstrated that Lyngbya sp., a filamentous cyanobacterium, can generate H2 in the presence of benzoate which is a central intermediate during the anaerobic degradation of many aromatic compounds. The highest H2 production rate of 17.05 μmol H2 /g Chla/h was obtained in the second cycle and 600 mg/L benzoate was depleted within 64 h in H2 production test. The strain has shown a higher H2 -producing capacity, which was comparable to those of certain noted strains such as N2 -fixing filamentous Anabaena variabilis PK84 and non-N2 -fixing filamentous Microcystis PCC 7806. The co-metabolism of benzoate for H2 production by Lyngbya sp. makes it an interesting model strain for clean energy production and hazardous pollutant removal. Graphical abstract: Highlights: Lyngbya sp. can generate H2 in the presence of benzoate. In H2 production test, 600 mg/L benzoate was depleted within 64 h. Lyngbya sp. has been proved as an excellent microbial species for clean energy production and hazardous pollutants removal.